2022
DOI: 10.2991/978-94-6463-008-4_56
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Psychology Empowerment on the Influence of Knowledge Sharing to Lecturer Performance: An Empirical Study in UBP Karawang

Abstract: Lecturers’ academic positions, university accreditation ratings, and lecturers’ education levels that are not yet optimal indicate that lecturers’ performance is still not optimal. The government’s efforts by providing scholarships, training, and grants are a form of empowering lecturers. In addition, there are research inconsistencies, which assume that knowledge sharing can improve lecturer performance is a concern, so the authors develop psychological empowerment variables as a form of renewal. The study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Creative performance or creativity is closely linked with innovative behavior (Abbas & Raja, 2015;Gomez & Rosen, 2001) and effectiveness (Bartram & Casimir, 2007), and can therefore lead to the formation of sensitive organizational structures (Mathieu et al, 2006). A strong relationship exists between psychological empowerment and knowledge sharing, which can significantly impact the performance faculty members (Suherman & Rismayadi, 2022). Psychological empowerment positively affects innovative work behavior (Tekin & Akgemci, 2019); hence, it can be said that innovative behavior starts with adaptation to change.…”
Section: Discussionmentioning
confidence: 99%
“…Creative performance or creativity is closely linked with innovative behavior (Abbas & Raja, 2015;Gomez & Rosen, 2001) and effectiveness (Bartram & Casimir, 2007), and can therefore lead to the formation of sensitive organizational structures (Mathieu et al, 2006). A strong relationship exists between psychological empowerment and knowledge sharing, which can significantly impact the performance faculty members (Suherman & Rismayadi, 2022). Psychological empowerment positively affects innovative work behavior (Tekin & Akgemci, 2019); hence, it can be said that innovative behavior starts with adaptation to change.…”
Section: Discussionmentioning
confidence: 99%
“…Junpahira & Pahlevi (2023) also believes that classroom action research is the efforts of teachers or practitioners in the form of various activities carried out to improve and/or improve the quality of learning in the classroom. Suherman et al (2023) explains that classroom action research is a form of research that is reflective, in which teachers carry out certain actions in order to improve or increase learning practices in the classroom in a more professional manner. From these various opinions, it can be concluded that classroom action research is research carried out by teachers in the classroom with the aim of improving or increasing their performance through self-reflection, which in the end is expected to increase students' understanding of learning concepts and their learning achievements.…”
Section: Methodsmentioning
confidence: 99%
“…The Discovery Learning model has six main steps in the learning stage, namely: Stimulation (providing stimulation), problem statement (problem identification), data collection (data collection), data processing (data processing), verification (proof), and generalization (concluding) (Hanifah, 2017;Hendrizal et al, 2022;Putri, 2020). The advantages of the Discovery Learning model according to Suherman et al (2022), namely that students are active in learning activities because they think and use their abilities to find the final result, students understand the learning material, because they experience the process of finding it themselves (Sahara et al, 2020), finding it themselves can create a sense of satisfaction, this inner satisfaction encourages them to make more discoveries so that their interest in learning increases, students who gain knowledge using the discovery method will be better able to transfer their knowledge to various contexts, and this method trains students to learn more on their own (Hayati, 2023;Lutfian, 2023;Tyas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%